On the Shapes of Tastes and Flavours - Spence, Charles; Deroy, Ophelia (Petits Propos Culinaires, 2012)
The article explores menu design based on notions of the correspondence between shapes and flavours and looks at the phenomenon of synesthesia in food and wine writing and at scientific investigations into cross-modal reception. Also investigates applications in the food industry for production and marketing.